Innovative 3D-printed educational models for vital pulp treatments and local anesthesia training in pediatric dentistry - Nagehan Aktaş; Didem Atabek; Osman Tunç (BMC Medical Education)
Abstract Background Preclinical training is essential across all areas of dental education. In pediatric dentistry, it is particularly valuable due to the unique challenges of working with young patients, and it provides a safe environment for students to gain confidence before transitioning to clinical care. Procedures such as local anesthesia administration and vital pulp therapy require specific skills that are best developed through simulation-based education. Recent advancements in three-dimensional (3D) printing technology offer innovative solutions to enhance dental education by providing realistic and patient-specific educational models. This study aimed to develop and evaluate two distinct 3D-printed educational models for pediatric dentistry training. Methods A patient-derived cone beam computed tomography dataset was processed to create anatomically accurate models replicating primary molar structures, pulp chambers, and surrounding hard tissues. Sixty-six dental students (third-year, fifth-year, and postgraduate) participated in hands-on training using these models. Participants assessed the models’ educational value, realism, and effectiveness using a structured survey. Results 68.2% of students strongly agreed, and 28.8% agreed that the local anesthesia model enhanced their understanding of anatomical structures and injection sites. Additionally, 81.8% strongly agreed, and 18.2% agreed that visualizing anesthetized nerves enhanced their understanding of how anesthesia spreads within the tissue. In vital pulp therapy training, 71.8% of participants strongly agreed, and 27.3% agreed that the 3D-printed teeth provided a realistic simulation for pulp therapy procedures. 83.3% of students desired to use these models for more advanced methods, and 100% of third-year students strongly agreed that practicing 3D-printed models before treating actual patients would be beneficial. Compared to phantom and extracted teeth, 3D-printed models were perceived as more engaging and accessible, though extracted teeth remained superior in tactile authenticity. Conclusions 3D-printed models contribute to a more structured and comprehensive educational process by bridging the gap between theoretical knowledge and hands-on experience. Integrating 3D printing technology into the dental curriculum has excellent potential to improve the quality of pediatric dentistry education and clinical preparation. Clinical trial number Not applicable.